Evaluación del estado nutricional, patrones de consumo alimentario y de actividad física en escolares del Cercado de Lima - Aparco, Juan Pablo (2016)
Objectives. To assess the nutritional status, physical activity, and eating habits of schoolchildren in Cercado de Lima (Lima district). Materials and methods. Cross-sectional descriptive study. The sample included schoolchildren from first to fourth grade in four public elementary schools located in Cercado de Lima. The study variables were nutritional status, hemoglobin dose, physical activity, and eating habits. The percentages of the qualitative variables and central tendency measures for quantitative ones were calculated. The t-test and chi-squared test were applied to analyze differences between both genders. Results. Of 824 schoolchildren included in the study, 24% were obese, 22% were overweight, 5% had short stature, and 11.9% had anemia; in all instances, there were no substantial gender differences. More than 40% of schoolchildren would eat crackers and drink packaged juice and/or soda two or more times a week. In addition, 28% of schoolchildren were inactive; there were significant differences in both genders (P<0.05). Conclusions. Obesity is an ongoing problem with higher rates than overweight and, together, the aforementioned problems affect almost 50% of schoolchildren surveyed. Similarly, the study revealed patterns associated with a sedentary lifestyle and frequent consumption of foods with high levels of sugar, salt, and/or fats.